Exploring the benefits of e-learning for life and earth sciences education in Moroccan high schools - Rachad, Sofia; Oughdir, Lahcen (Journal of Education and e-Learning Research, 2023)
The reliance on online learning systems has increased during the COVID-19 epidemic to maintain education. The effectiveness of online life and earth science instruction is assessed in this study which involves 150 first-year high school students. Methodologically, it juxtaposes e-learning with traditional classroom teaching across various parameters. The study reveals that digital learning yielded better results across all considered variables (p < 0.05), irrespective of student gender (p = 0.216). Better performance was seen in subjects such as "man and the environment" and "greenhouse effect and climate change" when learning was carried out online (p < 0.001). However, no notable scoring differences were found in practical subjects such as " creation of ecological reserves to preserve biodiversity," "clean technologies to protect the environment" and " environmental education and sustainable development," (p = 0.627 and p = 0.147). Thus, e-learning proves to be a useful supplement to traditional instruction. It shouldn't be used in place of hands-on activities in all situations.